FROM INDUSTRIAL TO INFORMATION SOCIETY - Sommer, Michael (Journal of European Economy, 2018)
The analysis of the factors that stimulate transition to the information economy and the accompanying trends in development allows to outline more clearly and logically a set of questions that demand state regulation. Changes in the economic system create preconditions to the formation of a new type of labour relations in the labour market. In view of this, a proposed mechanism for realizing and balancing interests and social protection of the employed is of significant interest to both theorists and practicians.